Definir un fantasma : Lo real en Óscar Muñoz - Barbeito Andrés, Leticia (2018)
In the context of the ontology of photography, what is real is suggested as the key to approach the work by the Colombian artist Óscar Muñoz. The corpus of selected pieces is an invitation to problematize the epistemological definitions of the discipline. In this line, we revised some authors who built the classic photographic theory of the 20th century, as well as those authors that have recently stated the categories of expanded photography and post-photography, which are still under development.